Career consequences of HIV-related stigma in organizations: A conservation of resources perspective - Decoste, Anthony (Animo Repository, 2019)
Drawing on conservation of resources theory, this study examined the relationships among HIVrelated stigma, negative psychological states, job performance (i.e., in-role performance and organizational citizenship behaviors, OCBs) and career success (i.e., career satisfaction and promotability) of employed individuals who are living with HIV. It also examined the role of CD4 count and perceived organizational support (POS) in moderating these mediated relationships A three-wave longitudinal survey administered at three-month intervals made use of multisource data by recruiting participants from two separate HIV treatment clinics in Metro Manila, Philippines (Study 1). In addition, a seven-week quantitative diary study administered on a weekly basis was conducted using data from participants receiving treatment in three separate HIV treatment clinics, also in Metro Manila. In both studies, a biological indicator was abstracted from the participants’ medical records. All participants were employed at least 20 hours per week and were receiving antiretroviral therapy at the time of data collection. Results from Study 1 suggest that 1) Time 1 HIV-related stigma was negatively associated with Time 2 negative psychological states; 2) Time 2 negative psychological states were negatively associated with Time 2 in-role performance and Time 2 OCBs; 3) Time 2 in-role performance was positively related to Time 3 career satisfaction; 4) Time 2 OCBs were positively related to Time 3 promotability; 5) negative psychological states mediated the relationship between HIVrelated stigma and job performance; 6) the conditional indirect effects of HIV-related stigma on in-role performance and OCBs via negative psychological states were stronger for high (i.e., low CD4 count) as opposed to low (i.e., high CD4 count) HIV progression. These results were replicated in Study 2 at the within-person level. However the following differences were noted: At the within-person level 1) OCBs were positively associated with career satisfaction, contrary to Study 1; 2) there was a full mediation of negative psychological states between HIV-related stigma and in-role performance, compared to a partial mediation in Study 1; 3) the relationship between negative psychological states and career satisfaction via job performance was partially mediated when job performance was operationalized as OCBs; 4) the relationship between HIVrelated stigma and career satisfaction was serially mediated via negative psychological states and OCBs; and 5) none of the conditional indirect effects were supported. In sum, this study contributes to the literature in several important ways, namely it introduces a biological indicator in management research; highlights new opportunities for multidisciplinary research; provides insights emanating directly from HIV-positive employees; provides insights for government administrators, legislators, and corporate decision-makers; and demonstrates that HIV progression takes a longer period of time to moderate the relationships between HIV-related stigma and negative psychological states.